Budget deficit, size of the public sector and majority voting - Jens Siebel (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2005)
In this paper Tabellini's and Alesina's (1990) median voter model for the explanation of budget deficits is modified by endogenizing the private sector. Debt finance is supplemented by taxing a private consumption which serves as an additional source of revenue for funding the public sector. The introduction of the private sector enables us to explain the budget balance as a result of political polarization with a left-wing party and a right-wing party having different preferences for the size of the public sector.
Keywords: H61; H62; 330; Haushaltsdefizit; Finanzpolitik; Staatsquote; Median Voter; Theorie